The Adsorption and Sensing Performances of Ir-modified MoS2 Monolayer toward SF6 Decomposition Products: A DFT Study - Hongcheng Liu; Feipeng Wang; Kelin Hu; Tao Li; Yuyang Yan; Jian Li (Nanomaterials, 2021)
In this paper, the Ir-modified MoS2 monolayer is suggested as a novel gas sensor alternative for detecting the characteristic decomposition products of SF6, including H2S, SO2, and SOF2. The corresponding adsorption properties and sensing behaviors were systematically studied using the density functional theory (DFT) method. The theoretical calculation indicates that Ir modification can enhance the surface activity and improve the conductivity of the intrinsic MoS2. The physical structure formation, the density of states (DOS), deformation charge density (DCD), molecular orbital theory analysis, and work function (WF) were used to reveal the gas adsorption and sensing mechanism. These analyses demonstrated that the Ir-modified MoS2 monolayer used as sensing material displays high sensitivity to the target gases, especially for H2S gas. The gas sensitivity order and the recovery time of the sensing material to decomposition products were reasonably predicted. This contribution indicates the theoretical possibility of developing Ir-modified MoS2 as a gas sensor to detect characteristic decomposition gases of SF6.